2016
DOI: 10.1111/acel.12435
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of age‐associated exhausted CD8+ T cells defined by increased expression of Tim‐3 and PD‐1

Abstract: SummaryAging is accompanied by altered T‐cell responses that result in susceptibility to various diseases. Previous findings on the increased expression of inhibitory receptors, such as programmed cell death protein 1 (PD‐1), in the T cells of aged mice emphasize the importance of investigations into the relationship between T‐cell exhaustion and aging‐associated immune dysfunction. In this study, we demonstrate that T‐cell immunoglobulin mucin domain‐3 (Tim‐3), another exhaustion marker, is up‐regulated on ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 40 publications
(80 reference statements)
3
68
1
Order By: Relevance
“…Interestingly, this study was the first to reveal that the expression of TIM-3 on cytotoxic T cells significantly increased in patients with BD, which tented to negatively associate with the score of MADRS. As documented, TIM-3 not only plays a crucial role in mediating the exhaustion of cytotoxic T cells1417, but also presents as a potent suppressor of cytotoxic T cell inflammation27. Blockade of TIM-3 pathway can help to restore the adaptive immunity28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this study was the first to reveal that the expression of TIM-3 on cytotoxic T cells significantly increased in patients with BD, which tented to negatively associate with the score of MADRS. As documented, TIM-3 not only plays a crucial role in mediating the exhaustion of cytotoxic T cells1417, but also presents as a potent suppressor of cytotoxic T cell inflammation27. Blockade of TIM-3 pathway can help to restore the adaptive immunity28.…”
Section: Discussionmentioning
confidence: 99%
“…Programmed cell death protein 1 (PD-1) also functions as an inhibitory immune checkpoint and negatively regulates immune response1516. Moreover, TIM-3 and PD-1 both may weaken CD8+ T-cell function and induce T-cell exhaustion17. PD-L1 and PD-L2, two ligands of PD-1, and their interaction with PD-1 are correlated with T cell activation and tolerance1819.…”
mentioning
confidence: 99%
“…Tim-3 and PD-1 take part in control negative regulation of immune responses in many diseases (34), establishing the balance between the activation and inhibition of T cells, with a tendency towards the latter. We found that the expression of Tim-3 on CD4 + T cells and PD-1 on CD8 + T cells was notably lower in AS, which implied that Tim-3 and PD-1 on T cells could affect the disease.…”
Section: Discussionmentioning
confidence: 99%
“…While exhausted CD8 + T cells triggered by just age in the absence of infection have been described in the mouse, similar evidence for humans is lacking (Lee et al, 2016). However, some of the pathways that induce T cell exhaustion may be shared with those that are involved in T cell aging and senescence.…”
Section: Age and T Cell Exhaustionmentioning
confidence: 99%